(untitled) (Research, Society and Development, 2022)
The objective is to characterize and analyze the anomalous rainfall between the municipalities of Alagoa Nova and Lagoa Seca, understanding the anomalous climate oscillations, with the probable influence and occurrence of El Niño and La Niña climate phenomena, in the citrus and horticulture sector, and the calculation of rainfall anomalies. We used the total annual rainfall for the period 1983-2019 for the municipalities of Lagoa Seca and Alagoa Nova - Paraíba and performed the classification according to the intensity of El Niño and La Niña phenomena, calculating their annual anomaly taking into account their respective averages. However, do not rule out that in most years with negative anomalies occurred so equal to La Niña and El Niño phenomena, the opposite can be registered for the case of El Niño that occurred negative anomalies and La Niña positive anomalies both of increased or reduced intensity. Therefore, it can not be said that ENSO has not influenced the local rainfall in the regions studied, and that ENSO is not the main climatic and/or environmental element contributing to the occurrence of extreme rainfall events. It is necessary to evaluate other climatic phenomena and the regional environmental profile in order to justify the rainfall variability. The influence of local factors on the spatial distribution of rainfall is evident in the El Nina and La Nina graphs, highlighted by the anomalies. The rainfall concentration is due to the favorable controlling factors, relief, approach to the Borborema plateau and the vegetation. The lower accumulations were caused by the cooling of the tropical Atlantic and the blockages in the local and regional systems.